A Twisted Dimeric Perylene Diimide Electron Acceptor for Efficient Organic Solar Cells. Issue 13 (13th May 2014) - Lin, Yuze; Wang, Jiayu; Dai, Shuixing; Li, Yongfang; Zhu, Daoben; Zhan, Xiaowei
<x xml:space="preserve">Abstract</x> A novel solution‐processable twisted dimeric perylene diimide (IDT‐2PDI) with a bulky fused‐ring indacenodithiophene as a bridge is developed as an electron acceptor for organic solar cells (OSCs). Poly(3‐hexylthiophene) (P3HT):IDT‐2PDI based OSCs have power conversion efficiencies (PCEs) up to 2.61% with a high fill factor of 0.668, and benzodithiophene‐diketopyrrolopyrrole (BDT‐2DPP):IDT‐2PDI based OSCs exhibit a promising PCE of 3.12%. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>